Genome-wide identification and characterization of stress-associated protein (SAP) gene family encoding A20/AN1 zinc-finger proteins in Medicago truncatula - Zhou, Yong; Zeng, Liming; Chen, Rongrong; Wang, Yihua; Song, Jianbo (Archives of Biological Sciences, 2018)
Stress associated proteins (SAPs) play important roles in developmental processes, responses to various stresses and hormone stimulation in plants. However, little is known about the SAP gene family in Medicago truncatula. In this study, a total of 17 MtSAP genes encoding A20/AN1 zinc-finger proteins were characterized. Out of these 17 genes, 15 were distributed over all 8 chromosomes at different densities, and two segmental duplication events were detected. The phylogenetic analysis of these proteins and their orthologs from Arabidopsis and rice suggested that they could be classified into five out of the seven groups of SAP family genes, with genes in the same group showing similar structures and conserved domains. The cis-elements of the MtSAP promoters were studied, and many cis-elements related to stress and plant hormone responses were identified. We also investigated the stress-responsive expression patterns of the MtSAP genes under various stresses, including drought, exposure to NaCl and cold. The qRT-PCR results showed that numerous MtSAP genes exhibited transcriptional responses to multiple abiotic stresses. These results lay the foundation for further functional characterization of SAP genes. To the best of our knowledge, this is the first report of a genome-wide analysis of the SAP gene family in Medicago truncatula. https://doi.org/10.2298/ABS170529028Z Received: May 29, 2017; Revised: July 28, 2017; Accepted: July 31, 2017; Published online: August 24, 2017 How to cite this article: Zhou Y, Zeng L, Chen R, Wang Y, Song J. Genome-wide identification and characterization of stress-associated protein (SAP) gene family encoding A20/AN1 zinc-finger proteins in Medicago truncatula. Arch Biol Sci. 2018;70(1):87-98.